DENGUE FEVER: A REVIEW OF EPIDEMIOLOGY, CLINICAL FEATURES, AND PREVENTION (Journal of Medical & Health Sciences Review, 2025)
Dengue fever is an acute, mosquito-borne viral disease of major global health importance, transmitted primarily by Aedes aegypti and Aedes albopictus mosquitoes. The infection is caused by any of the four antigenically distinct dengue virus serotypes (DENV-1 to DENV-4), resulting in a clinical spectrum ranging from mild febrile illness to severe manifestations such as dengue hemorrhagic fever and dengue shock syndrome. This review article compiles key findings from peer-reviewed studies and international guidelines to summarize the virology, transmission cycle, pathophysiology, clinical features, diagnostic approaches, management strategies, and preventive measures for dengue. Globally, an estimated 390 million infections occur annually, with a rising trend attributed to rapid urbanization, climate change, and inadequate vector control. Current management remains supportive, focusing on timely recognition of warning signs, careful fluid resuscitation, and prevention of complications. Prevention relies on integrated vector control, community education, and selective vaccination. This review highlights the urgent need for strengthened surveillance, sustainable mosquito control, and continued research into antivirals and vaccines to mitigate dengue’s growing burden.